RESPON STRUKTUR TERHADAP BEBAN DINAMIK GEMPA PADA RUSUN MAHASISWA INSTITUT TEKNOLOGI PADANG DENGAN SHEARWALL - Ibnu Hanif Sudarmaka; Rafki Imani; Rita Nasmirayanti; Kharisma Permata Sari (Program Studi Teknik Sipil, 2023)
Rusun Mahasiswa ITP Padang was originally designed without using a shearwall, but in practice, it was changed to using a shearwall with L-frame type. This study aims to analyze the effect of using shearwall on the columns and beams of Rusun Mahasiswa ITP Padang. The results showed that the use of shearwall with L-frame type on columns caused a 3% decrease in the axial force on the column, up to 90% in cross-sectional force, and up to 84% in moment load reduction. Meanwhile, the beam elements can reduce the shear force by up to 24%, and the moment load can be reduced by up to 35%. The deviation between floors in Rususn Mahasiswa ITP Padang has met the required limit, where the deviation values for the x direction (Î”x) and y direction (Î”y) are smaller than the permit deviation (Va).